Parental Participation in Preterm Infant Feeding in the Neonatal Intensive Care Unit. Issue 2 (March 2023) - Nist, Marliese Dion; Robinson, Audrey; Pickler, Rita H.
Abstract: Purpose: To identify factors associated with parental participation in the feeding care of hospitalized preterm infants and determine associations between parental participation in feeding and infant neurobehavioral outcomes. Study Design and Methods: Secondary analysis of data collected during a larger study of preterm infants. Parental participation in gavage and oral feeding was measured as a proportion of all feeding opportunities. Neurobehavioral outcomes were measured using a neurobehavioral assessment and feeding milestones. Other data were collected from the electronic health record. Results: Parental participation in feeding was low. There were associations between parental participation in gavage feeding and infant sex, insurance type, maternal race, infant gestational age at birth, and birthweight. There were associations between parental participation in oral feeding and infant sex, insurance type, maternal race, and study group. Greater parental participation in feeding was associated with earlier achievement of some feeding milestones. Clinical Implications: Parental participation in feeding can decrease the time required for infants to achieve feeding milestones, possibly leading to decreased length of hospitalization. Nurses should encourage parents to participate in caregiving for their preterm infants. Interventions are needed to remove barriers to parental participation in caregiving. Abstract : In this secondary data analysis of 87 preterm infants using data from a randomized controlled trial of patterned tactile experience provided during gavage and oral feeding on infant neurobehavior and clinical outcomes, parental involvement in infant feeding in the neonatal intensive care unit was low. Parental participation in feeding can decrease the time required for infants to achieve feeding milestones, possibly leading to decreased length of hospitalization. Nurses should encourage parents to participate in caregiving for their preterm infants. Interventions are needed to remove barriers to parental participation in caregiving.